The Effects of Substituting Glassware for Plasticware and the Use of an Ethanol Vector on Oocyte Maturation In Vitro - A. D. Macaulay; C. K. Hamilton; P. M. Bartlewski; W. A. King (Veterinary Medicine International)
The intent of this study was to evaluate specific technical aspects of in vitro oocyte maturation (IVM), which included container material and solvent delivery vector. Oocytes were matured in oil-free, open-well systems contained in either plastic or glass dishes and compared to control oocytes matured in media droplets on plastic dishes overlaid with mineral oil. Open-well experiments were repeated with ethanol in a quantity sufficient for delivery of nonmiscible compounds. Cleavage rates were significantly decreased in the glassware system when compared to controls. The plasticware open-well system did not differ from either the controls or the glassware groups. Cleavage in glassware with ethanol was significantly lower than controls or plasticware with ethanol. Blastocyst rates were only decreased in the glassware-ethanol treatment when compared to plasticware-ethanol treatment. Cell counts and percentage of TUNEL-positive cells did not differ significantly. Unexpectedly, sex ratio was significantly decreased (34% male) from the expected value of 50% male in the glassware group with added ethanol. The current study demonstrates the sensitivity of IVM to subtle technical changes, resulting in significant developmental consequences.